A Study of Prevalence of Yoga Education in Schools - Yadav, Saroj; Singh, Sweta; Sharma, Shruti (JOURNAL OF INDIAN EDUCATION, 2020)
Yogic practices are important for every human being, especially for children not only for gaining physical fitness, but also to develop learning, memory and dealing with stress and anxieties in children. The commencing of yoga education in school curriculum has been emphasised as a follow-up of the International Yoga Day, announced by the General Assembly in 2015. Therefore, the aim of the paper is to study the implementation of yoga in schools through a study of the status of different yogic activities conducted in schools of KVS, NVS, CBSE and other schools of Delhi. The findings of the research reveals that, a bulk of Indian schools have acknowledged and incorporated yoga and yogic practices as a part of their core curriculum, and dedicated a separate period where student can practice yoga and its allied practices. Still, in order to make precise scrutiny of the effect of yoga on school going students, a certain degree of standardisation has to be brought about.